Comparison of electromagnetic guided imagery to standard confirmatory methods for ascertaining nasogastric tube placement in children. Issue 4 (11th May 2021) - Wathen, Beth; McNeely, Heidi L.; Peyton, Christine; Pan, Zhaoxing; Thomas, Robin; Callahan, Cayla; Fidanza, Sara; Brown, James; Neu, Madalynn
Abstract: Purpose: Evaluate the accuracy of an electromagnetic device (EMD) guided nasogastric tube (NGT) placement compared with standard confirmation methods. A secondary aim was to determine if EMD guided NGT placement would avert potential pulmonary misplacements of the tube. Design and Methods: Pediatric Intensive Care Unit (PICU) patients were enrolled if they had an NGT order during the study period of April 2014 through December 2016. Patients were included if they were one through 18 years of age. An EMD trained nurse inserted the NGT using EMD guidance. An insertion questionnaire, confirming if the nurse determined the NGT to be gastric per EMD, was completed immediately after NGT placement and before confirmation via either pH testing or radiographic imaging. Results: Forty‐five patients were enrolled in the study. Nurses reported, based on EMD, that 86.7% ( n  = 39) of placements were gastric. Overall agreement between EMD guided tube placement and pH testing was 58% ( n  = 26). The marginal distribution was significantly different between the two methods ( p  = .0029). When compared to radiographic confirmation, sensitivity of the pH method was 32% (95% confidence interval [CI]: 17%–51%) compared with 85% (95% CI 69%–95%) for the EMD method. Conclusions: EMD guidance was superior to pH testing when compared with radiographic confirmation of nasogastric tube placement in children. Practice Implications: EMD guided NGT placement is a potentially viable method for confirming nasogastric tube placement in children when done by appropriately trained clinicians. More research on EMD guided NGT placement in children is needed before any practice recommendation can be made.